Revegetation and Tourism Development as an Environmental Recovery Effort on Post-Mining Marble Land in Tulungagung, East Java, Indonesia - Krisna Tanno Kakauhe; Srie Muljani; Erwan Adi Saputro (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
As a national marble production center, mining activities in Tulungagung Regency, East Java, contribute significantly to the regional economy. However, behind these benefits come complex ecological and social pressures. This study aims to analyze the impacts of marble mining on local communities and the surrounding ecosystem, and to evaluate environmental restoration strategies through revegetation and tourism development on post-mining land. Using a mixed-methods approach with a case study design, this research combines quantitative surveys, in-depth interviews, field observations, and analysis of supporting documents. The results revel a dilemma: mining increases local incomes and opens business opportunities, but simultaneously triggers land degradation, decreases water and air quality, and changes the community’s socio-ecological structure. Revegetation efforts using local species have proven effective in stabilizing the soil and encouraging the potential for ecosystem recovery. Meanwhile, community-based tourism development facilitated by Village-Owned Enterprises (BUMDes) offers a path to post-mining economic diversification. This integration of ecological rehabilitation and sustainable tourism serves as a strategic model for transforming post-mining land into productive spaces that support the achievement of the Sustainable Development Goals (SDGs). This research emphasizes the importance of an integrated socio-ecological approach in managing post-mining areas.